Human Immunodeficiency Virus Type 1 Envelope Glycoproteins That Lack Cytoplasmic Domain Cysteines: Impact on Association with Membrane Lipid Rafts and Incorporation onto Budding Virus Particles - Bhattacharya, Jayanta (American Society for Microbiology, 2004)
The human immunodeficiency virus type 1 (HIV-1) envelope comprises a surface gp120 and a transmembrane gp41. The cytoplasmic domain of gp41 contains cysteine residues (C764 and C837) which are targets for palmitoylation and were reported to be required for envelope association with lipid rafts and assembly on budding virions (I. Rousso, M. B. Mixon, B. K. Chen, and P. S. Kim, Proc. Natl. Acad. Sci. USA 97:13523-13525, 2000). Several infectious HIV-1 clones contain envelopes that have no gp41 cytoplasmic cysteines. Since no other gp41 amino acid is a target for palmitoylation, these clones imply that palmitoylation is not essential for envelope trafficking and assembly. Here, we show that HIV-1 envelope mutants that lack gp41 cytoplasmic cysteines are excluded from light lipid rafts. Envelopes that contained residues with bulky hydrophobic side chains instead of cysteines retained their association with heavy rafts and were nearly fully functional for incorporation into virions and infectivity. Substitution of cysteines with alanines or serines eliminated raft association and more severely reduced envelope incorporation onto virions and their infectivity. Nevertheless, the A764/A837 mutant envelope retained nearly 40% infectivity compared to the wild type, even though this envelope was excluded from lipid rafts. Our results demonstrate that gp41 cytoplasmic cysteines that are targets for palmitoylation and are required for envelope trafficking to classical lipid rafts are not essential for HIV-1 replication.